Numerical Prediction of Thermal Storage Using Phase Change Material - Sami, S.; Tardy, F. (Journal of Technology Innovations in Renewable Energy, 2015)
A numerical mathematical model has been developed to predict the thermal behavior of phase change material during thermal storage. The model includes the effects of various mechanisms of heat transfer such as conduction, convection as well as fusion of the phase change material. Water/Ice was used as a phase change material. The thermal behavior of the phase change material during cooling has been studied experimentally and analyzed under different conditions. Comparisons were made against experimental data for validation of the predictive model. The model fairly predicted experimental data obtained at various inlet conditions.